Strategi Public Relations Dalam Rebranding Bekasi Square Menjadi Revo Town - Sumiyati Sumiyati; Euis Komalawati; Angelika Rosma (LUGAS Jurnal Komunikasi, 2019)
The main purpose of the research is to know how the Public Relations’ strategy of rebranding Bekasi Square for Revo Town. This research method used qualitative descriptive approach with a study case method. The technique of collecting data through in-depth interviews, documentation, and literature studies. Based on the research results, the rebranding stages’ strategy of Bekasi Square for Revo Town are carried out through four stages, namely fact-finding, planning-decision, communication-action, and evaluation. At the first stage, it is known the reason for rebranding Revo Town is the existence of fierce competition in the field of modern retail and to make repairs and rejuvenation of Revo Town. At the planning-decision stage there is a rebranding factor, namely the acquisition of Revo Town by Farpoint and the number of malls that grow and develop in Bekasi, the purpose of rebranding is to show Revo Town commitment and improve the quality. In the communication-action phase there is a rebranding process, namely repositioning where Revo Town further strengthens the Revo Town brand as a textile mall in Bekasi. Renaming Revo Town is by changing the name of Bekasi Square to Revo Town. Redesigning Revo Town includes changes to the logo that currently dominates using orange, and changes the Revo Town tagline to simply a place for togetherness and family quality time. Relaunching Revo Town was held by holding a press conference and distributing press releases. The evaluation stage in Revo Town rebranding is done every six months by giving a questionnaire to the tenants and visitors of Revo Town.